KECENDERUNGAN INDEKS PRESTASI KUMULATIF (IPK) MAHASISWA YANG BEKERJA - Novianti Rahmawati; Norhayatun Norhayatun; Muhammad Rifan (STKIP MUHAMMADIYAH SAMPIT, 2018)
Student which lecture without working in the reality own the low IPK though no double responsible and reason making student which do not work the to leave responsible as purification student making its IPK low. however others also there student which do not work but achievement remain to in the field of this academic. This is proved by IPK high obtained. This research is to know the difference Make An Index To The Cumulative Achievement (laboring IPK) Student and do not work. Population in this research is entire/all Economic student Prody and BK amounting to 238 student. Technique analyse the data used is test of Mann Whitney. Result from this research the existence of difference Make An Index To The Cumulative Achievement ( laboring IPK) Student and do not put hand to the student of STKIP Muhammadiyah Sampit of year akademik 2015 / 2016. Higher student employee scores of 15.79% compared with the non-working student's IPK of 6.29%. The difference is 9.5%.